Development of a Low-Cost Colorimeter Based on LED Light Sources - Aldini, Ittaka; Kim, Soochan (International Journal of Engineering and Technology, 2018)
The spectrophotometric and colorimetric methods are the most widely used methods in various scientific fields, such as physics, materials science, chemistry, biochemistry, and molecular biology. They are based on an application of the Beer and Lambert law. However, the currently available instruments for spectrophotometry and colorimetry mostly use a light source, grating disc, and a silicon photocell. Unfortunately, the use of all these components in combination increases the device costs. The proposed system was developed with a low-cost material, a light emitting diodes (LED) as the light source, and an RGB Sensor. Two types of LEDs having different wavelengths were selected for each solution. The USB serial (through a USB cable) and wireless Bluetooth (the Bluetooth module) were the two alternative communication methods used to control the system and view the results. The measurement range was 0.02 to 30.0 ppm. The colorimeter was successfully used to detect nitrate and fluoride concentrations with an average R2 of 0.99 when compared with the concentrations obtained by using a spectrophotometer (Optizen POP QX, Mecasys, South Korea). The material cost was less than $75.Â Â Â